Penentuan Nilai Resolusi Spasial Pada Citra Ultrasonik Metode Time of Flight Menggunakan Fungsi Sebaran Titik (Point Spread Function) - Wahyu Fredi Santoso; Suryono Suryono (Youngster Physics Journal, 2012)
Abstrsct Ultrasonic wave have been familiarly applicable in many fields, imaging system is one of example. Spatial resolution value from obtained image plays important role in imaging system, therefore it could defining smallest object which detectable by its imaging system. On the research of determining spatial resolution is done using point spread function (PSF). Ultrasonic wave imaging system which have been conducted consist of transmitter and receiver series, mechanic activator, microcontroller series and also interfaces application and time of flight splitter. Transmitter series is uses to obtaining ultrasonic wave by vibrating high voltage ultrasonic transducer. Receiver series is used to receiving reflection wave from the object before it used as interruption logical at microcontroller counter. Mechanic activator required to activates ultrasonic transducer. In the other side, microcontroller series also used as transmitter and receiver series and mechanic activator controller, time of flight splitter and timer, and also to doing serial communication with the computer. Interface application and Time of Flight splitter used to doing Time of Flight data acquisition from microcontroller. Image spatial resolution defines by fitting edge spread (ESF) function data. Afterwards, defining line spread function (LSF) value which obtained by first differential from edge spread function (ESF). Spatial resolution defining process ends by fitting line spread function then full width at half maximum (FWHM) value could be obtained. FWHM is the spatial resolution value of obtained image from imaging system. The result shows image spatial resolution value which obtained from ultrasonic wave imaging system is 0,35cm with standard deviation 0,03cm. Keyword: point spread function, spatial resolution, Time of Flight, full width at half maximum (FWHM).